Assessment of Public Transport Footway Facilities Bogor District - Arifin, Wahyudin (ASTONJADRO, 2023)
Along with the increasing need for travel and the high dependence on motorized vehicles, the growth of existing transportation facilities and infrastructure is ultimately unable to accommodate these needs and leads to traffic jams, such as pollution, a decrease in the quality of life of the community and the level of road safety. Studies conducted at stations and Cibinong Terminal to analyze pedestrian characteristics and facilities. The research method used is direct observation and data collection in the field. From the results of the analysis in the direction of jl. Raya Bogor to Pabuaran with a vehicle volume of 2,160 per / hour on Monday afternoons at LOS B, the direction of Bogor to Jakarta with a vehicle volume of 13,390 on Tuesday and Saturday with peak hours in the afternoon, there is LOS E, and in the direction of Ciriung to Cikaret there is LOS B from morning to evening. The number of pedestrians is based on age with the direction of entering and exiting stations, stops and terminals, such as Cibinong Terminal with adult male pedestrians 16-40 years old, with the volume of pedestrians from and to the station. The density occurs on Monday afternoons. Tuesday morning, noon and evening, and Terminal on Wednesday morning. with the results of interviews of respondents who are at the productive age of 18-45 years, with high school / vocational school graduation with an income of 3-6 million and an expense of 1-2 million, the traveling characteristics of most respondents use station facilities, respondents are willing to walk 501-600 m, the level of facility in the respondent's station is quite satisfied, in the terminal the respondent is not satisfied, especially with the safety of pedestrians. Special satisfaction of Taxi / Ojek / delivery users and parking lots, respondents are quite satisfied, especially in the ease of finding a vehicle, the satisfaction of users of public transportation of respondents is quite satisfied, especially in the ease of finding a vehicle. The results of this study are the construction of pedestrian facilities and zebra crossing facilities.